The Puzzling Fate of a Lupin Chromosome Revealed by Reciprocal Oligo-FISH and BAC-FISH Mapping - Bielski, Wojciech; Książkiewicz, Michał; Šimoníková, Denisa; Hřibová, Eva; Susek, Karolina; Naganowska, Barbara (Genes, 2020)
Old World lupins constitute an interesting model for evolutionary research due to diversity in genome size and chromosome number, indicating evolutionary genome reorganization. It has been hypothesized that the polyploidization event which occurred in the common ancestor of the Fabaceae family was followed by a lineage-specific whole genome triplication (WGT) in the lupin clade, driving chromosome rearrangements. In this study, chromosome-specific markers were used as probes for heterologous fluorescence in situ hybridization (FISH) to identify and characterize structural chromosome changes among the smooth-seeded (Lupinus angustifolius L., Lupinus cryptanthus Shuttlew., Lupinus micranthus Guss.) and rough-seeded (Lupinus cosentinii Guss. and Lupinus pilosus Murr.) lupin species. Comparative cytogenetic mapping was done using FISH with oligonucleotide probes and previously published chromosome-specific bacterial artificial chromosome (BAC) clones. Oligonucleotide probes were designed to cover both arms of chromosome Lang06 of the L. angustifolius reference genome separately. The chromosome was chosen for the in-depth study due to observed structural variability among wild lupin species revealed by BAC-FISH and supplemented by in silico mapping of recently released lupin genome assemblies. The results highlighted changes in synteny within the Lang06 region between the lupin species, including putative translocations, inversions, and/or non-allelic homologous recombination, which would have accompanied the evolution and speciation.
Keywords: Chromosomes, Plant; In Situ Hybridization, Fluorescence; chromosome evolution; wild species; Lupinus; oligo-painting; Genome, Plant; umělé bakteriální chromozomy; hybridizace in situ fluorescenční; oligonucleotide probes; Chromosome Mapping; cytogenetics; comparative-mapping; Chromosomes, Artificial, Bacterial; mapování chromozomů; chromozomy rostlin; genom rostlinný; FISH; lupin; karyotype evolution